2017
DOI: 10.5056/jnm16057
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microaspiration in the Pathogenesis of Gastroesophageal Reflux-related Chronic Cough

Abstract: Background/AimsGastroesophageal reflux disease (GERD) is one of the main causes of chronic cough. We evaluated the role of microaspiration in the pathogenesis of reflux-related cough by determining the amount of lipid-laden macrophages (LLMs) in bronchoalveolar lavage (BAL) specimens. MethodsA total of 161 cases of chronic cough were evaluated, and 36 patients (average age 48.2 years) were recruited for this single center prospective study. Patients with a history of smoking, angiotensin converting enzyme inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…5 Acid-suppressive drugs are considered effective and safe to use during pregnancy to treat gastroesophageal reflux disease (GERD), a common complication that is reported with up to 80% of pregnancies. 6,7 In adults, acidsuppressive drugs may alleviate asthma in patients with GERD, 8 but the drugs are also associated with allergic sensitization. Pali-Schöll and Jensen-Jarolim 9 showed that the impairment of gastric function is a documented risk factor for sensitization against oral proteins and drugs.…”
mentioning
confidence: 99%
“…5 Acid-suppressive drugs are considered effective and safe to use during pregnancy to treat gastroesophageal reflux disease (GERD), a common complication that is reported with up to 80% of pregnancies. 6,7 In adults, acidsuppressive drugs may alleviate asthma in patients with GERD, 8 but the drugs are also associated with allergic sensitization. Pali-Schöll and Jensen-Jarolim 9 showed that the impairment of gastric function is a documented risk factor for sensitization against oral proteins and drugs.…”
mentioning
confidence: 99%
“…Previously, several studies reported an increased number of eosinophils in several respiratory biological samples, including bronchoalveolar lavage samples, induced sputum and mucosal biopsies in patients with chronic cough and GER . However, not all studies yielded the same results , leading us to the conclusion that inflammation of the airway in patients with GER induced cough is controversial and needs further evaluation.…”
Section: Discussionmentioning
confidence: 96%
“…One important hypothesis concerning the mechanism of reflux‐induced cough is that proximal reflux and micro‐aspiration of gastric refluxate stimulate coughing by direct irritation of the respiratory tract. Previous studies have found that proximal acid reflux and aspiration of gastric contents (pepsin, bile acid, or lipid‐laden macrophages) can induce CC events. A recent study also found that volume clearance time and reflux burden play key roles in inducing coughing .…”
Section: Discussionmentioning
confidence: 99%